CONDITIONAL CO-MOVEMENT AND DYNAMIC INTERACTIONS: US AND BRIC EQUITY MARKETS - Singh, Amanjot; Singh, Manjit (Economic Annals, 2017)
The present study attempts to capture conditional or time-varying co-movement and dynamic interactions between the US and BRIC (Brazil, Russia, India, and China) equity markets across the sample period 2004 to 2014 by employing diverse econometric models. The sample period is further divided into three different sub-periods concerning the US financial crisis period, viz. pre-crisis, crisis, and post-crisis periods. The vector autoregression–dynamic conditional correlation–multivariate asymmetric generalized autoregressive conditional heteroskedastic [VAR-DCC-MVAGARCH (1.1)] model and Toda-Yamamoto’s (1995) Granger causality tests are employed for the purpose of overall analysis in a multivariate framework. The results report the existence of time-varying co-movement between the US and BRIC equity markets, whereby co-movement between the US and Brazilian markets is found to be the highest, followed by the Russian, Indian, and Chinese equity markets. Dynamic interactions are also registered between the respective US/BRIC comovements during different sub-periods. The results have important implications for market participants and policymakers.